2020
DOI: 10.1016/j.seizure.2020.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of EEG findings in 617 patients diagnosed with COVID-19

Abstract: Highlights We systematically reviewed 84 reports of EEG findings in COVID-19 encephalopathy. Common findings are diffuse slowing, periodic patterns and seizures/status. Frontal EEG findings support the putative viral entry via olfactory mucosa. EEG changes could be from systemic causes or due to direct brain involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
142
4
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 47 publications
8
142
4
5
Order By: Relevance
“…This adds to evolving literature indicating that seizures comprise a relatively small percentage of patients undergoing cvEEG monitoring in the setting of COVID-19 illness ( 13 , 14 ). Moreover, findings on interictal EEG such as focal slowing and epileptiform discharges appear to increase the likelihood of also recording electrographic seizures in this population.…”
Section: Discussionmentioning
confidence: 65%
“…This adds to evolving literature indicating that seizures comprise a relatively small percentage of patients undergoing cvEEG monitoring in the setting of COVID-19 illness ( 13 , 14 ). Moreover, findings on interictal EEG such as focal slowing and epileptiform discharges appear to increase the likelihood of also recording electrographic seizures in this population.…”
Section: Discussionmentioning
confidence: 65%
“…Two systematic review studies with similar clinical questions have been previously reported [32] , [33] . Our meta-analysis provided additional value to those studies.…”
Section: Discussionmentioning
confidence: 83%
“…COVID-19 patients displaying general states of confusion, agitation, unconsciousness altered mental state and seizure have prompted diagnostic testing [ 136 , 137 ]. Upon receiving a electroencephalograph, a common diagnostic tool for encephalopathy, 21% were indicative of encephalopathy [ 136 ].…”
Section: Sars-cov-2 Infection Of the Nervous Systemmentioning
confidence: 99%
“…This diagnosis increased to 74% in critical patients [ 138 ]. The most common background abnormality and the site was diffuse slowing and the frontal region, respectively [ 137 ]. Awareness of the symptoms of encephalopathy and diagnostic testing is important as the diagnosis is associated with a worse functional outcome and increase in mortality [ 134 ].…”
Section: Sars-cov-2 Infection Of the Nervous Systemmentioning
confidence: 99%